OP72 Myalgic encephalomyelitis/chronic fatigue syndrome and pregnancy: a mixed-methods systematic review. (26th August 2022) - Pearce, Mark; Slack, Emma; Pears, Katrina; Newton, Julia; Rankin, Judith
Abstract : Background: Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a fluctuating complex condition. More common in women than men, it tends to develop between mid-20s and mid-40s, including the main childbearing age (15–45 years). There are currently no systematic reviews summarising evidence relating to ME/CFS and pregnancy. The lack of quality assessed, and systematic summary evidence makes it harder for people with ME/CFS to make informed decisions about pregnancy, and harder for health care professionals to offer evidence-based care. This mixed methods systematic review aims to examine and summarise existing evidence relating to ME/CFS and pregnancy, both in relation to pregnancy outcomes and experiences of pregnancy but also the effect of pregnancy on ME/CFS severity and symptoms. Methods: This review followed a convergent segregated design. Seven electronic databases, relevant grey literature, reference lists of relevant reviews, and reference lists and citations of all included studies, were searched. Where necessary, authors were contacted for additional information. Studies of any design published in English, reporting on ME/CFS and pregnancy/postpartum (up to two years), risk of pregnancy outcomes with ME/CFS, or experiences during pregnancy for mother, partner or health and social care professionals following pregnancy with ME/CFS were included. Three researchers performed screening, data extraction and quality assessments independently. Qualitative and quantitative literature was analysed separately using thematic and descriptive syntheses, respectively (meta-analysis was not appropriate). Findings were integrated through configuration. Results: Searches identified n=2, 789 studies, n=10 met our inclusion criteria. There were five quantitative studies, two qualitative studies and three pieces of grey literature. Preliminary results suggest that evidence is conflicting. In the qualitative literature, one study suggested one participant thought pregnancy improved ME/CFS symptoms while the other noted a participant commented that ME/CFS may have adversely affected her pregnancy. Of the four quantitative studies that reported on ME severity during pregnancy, two suggested pregnancy negatively impacted on ME/CFS, one study found most women had no change in ME/CFS symptoms during pregnancy, and one found ME/CFS improved during pregnancy. Only one study reported on pregnancy outcomes, finding a higher rate of spontaneous abortions, and increased developmental and learning delays in infants born to mothers with ME/CFS. Conclusion: Current evidence on ME/CFS in pregnancy is limited, and findings are inconsistent. Studies are limited by small sample size and currently, there is no UK evidence. More high-quality research into ME/CFS and pregnancy is urgently needed to support the development of evidence-based guidelines on ME/CFS and pregnancy.